Irisin Serum Levels and Skeletal Muscle Assessment in a Cohort of Charcot-Marie-Tooth Patients - Colaianni, Graziana; Oranger, Angela; Dicarlo, Manuela; Lovero, Roberto; Storlino, Giuseppina; Pignataro, Patrizia; Fontana, Antonietta; Di Serio, Francesca; Ingravallo, Angelica; Caputo, Giuseppe; Di Leo, Alfredo; Barone, Michele; et al. (Frontiers in Endocrinology, 2022)
Background Charcot-Marie-Tooth (CMT) indicates a group of inherited polyneuropathies whose clinical phenotypes primarily include progressive distal weakness and muscle atrophy. Compelling evidence showed that the exercise-mimetic myokine irisin protects against muscle wasting in an autocrine manner, thus possibly preventing the onset of musculoskeletal atrophy. Therefore, we sought to determine if irisin serum levels correlate with biochemical and muscle parameters in a cohort of CMT patients. Methods This cohort study included individuals (N=20) diagnosed with CMT disease. Irisin and biochemical markers were quantified in sera. Skeletal muscle mass (SMM) was evaluated by bioelectric impedance analysis, muscle strength by handgrip, and muscle quality was derived from muscle strength and muscle mass ratio. Results CMT patients (m/f, 12/8) had lower irisin levels than age and sex-matched healthy subjects (N=20) (6.51 ± 2.26 vs 9.34 ± 3.23 ug/ml; p=0.003). SMM in CMT patients was always lower compared to SMM reference values reported in healthy Caucasian population matched for age and sex. Almost the totality of CMT patients (19/20) showed low muscle quality and therefore patients were evaluated on the basis of muscle strength. Irisin was lower in presence of pathological compared to normal muscle strength (5.56 ± 1.26 vs 7.67 ± 2.72 ug/ml; p=0.03), and directly correlated with the marker of bone formation P1PN (r= 0.669; 95%CI 0.295 to 0.865; p=0.002), but inversely correlated with Vitamin D (r=-0.526; 95%CI -0,791 to -0,095; p=0.017). Surprisingly, in women, irisin levels were higher than in men (7.31 ± 2.53 vs 5.31 ± 1.02 ug/ml, p=0.05), and correlated with both muscle strength (r=0.759; 95%CI 0.329 to 0.929; p=0.004) and muscle quality (r=0.797; 95%CI 0.337 to 0.950; p=0.006). Conclusion Our data demonstrate lower irisin levels in CMT patients compared to healthy subjects. Moreover, among patients, we observed, significantly higher irisin levels in women than in men, despite the higher SMM in the latter. Future studies are necessary to establish whether, in this clinical contest, irisin could represent a marker of the loss of muscle mass and strength and/or bone loss.